Possibility and advantages of producing an ultra-high performance concrete (UHPC) with ultra-low cement content. (1st March 2021) - Ding, Mengxi; Yu, Rui; Feng, Yuan; Wang, Siyu; Zhou, Fengjiao; Shui, Zhonghe; Gao, Xu; He, Yongjia; Chen, Luyi
Highlights: The effect of low cement content on the properties of UHPC is studied. A UHPC with ultra-low cement content is developed. The properties of UHPC with ultra-low cement content is evaluated. The microstructure of UHPC with ultra-low cement content is studied. The eco performance of UHPC with ultra-low cement content is presented. Abstract: This study aims to clarify the possibility and advantages of producing an Ultra-High Performance Concrete (UHPC) with ultra-low cement content. The UHPC matrix is designed on the basis of the improved Andreasen and Andersen particle packing model (A&A), and then up to 73% (wt.) of cement clinker is replaced by inactive fillers. After that, the effects of large quantity of inactive fillers on UHPC fresh and hardened behaviors are investigated. The experimental results indicate that the reduction of binder content is beneficial for improving the UHPC workability and decreasing its cracking risk. However, when the added cement clinker amount is reduced to about 245 kg/m 3 concrete, the compressive strength, durability and pore structure of UHPC deteriorate greatly. Hence, to guarantee the mechanical capacity and sustainable development of UHPC simultaneously, the modified A&A model should be used to design a dense meso-skeleton, while the minimum cement clinker amount can be reduced to about 280 kg/m 3 concrete. Additionally, the hydration kinetics and microstructure development of the newly designed UHPC are correspondingly analyzed and discussed.